Pré-campanhas eleitorais: o oculto e explícito em cenas contrapostas no cenário político - Freitas, Gilvanira Maria Xavier de (2009)
This research presents indications from the political field that lead to a situation of electoral competition, over time, political action, which begins even before the campaigns are announced. This is what has been popularly called the “electoral climate”. This specific period is called the pre-campaign, which is the object of this research. To highlight the pre-campaign means to enter the fluid universe of the rhythm of the electoral event, at the moment when the said and the unspoken are still veiled by the strategy of surprise, of experimentation. The pre-campaign is inserted in the political field as an important moment in the construction of the social universe of electoral campaigns, since it has a dimension of ritualized construction in which the dynamics of the electoral event are being structured, allowing the perception of meanings that precede and they convey the political practices that prevail in times of election. The research emphasizes the extent to which pre-campaigns are inserted in the political field as an important moment in the construction of the social universe of electoral campaigns, since it has a dimension of ritualized construction in which one perceives the dynamics of the electoral event being structured, allowing the perception meanings that precede and convey the political practices that prevail in times of election. Thus, although it suggests that pre-campaigns are appendages to electoral campaigns, they prove to be ritualized passages of the political event, as they assume a structuring character of electoral plots. They enter in order to manage a new dynamic in the political sphere, setting an inaugural presentation time for those who intend to stand out, signaling interdictions from the political world. Pre-campaigns reveal substances of political life, caused by the spatial circumstance in which a candidacy is built in a space not shared with voters, or not so much, as in campaigns; space of dispute in which the focus is the candidate-voter relationship, considering the campaigns as scenarios for the realization of the political world, with actors and situated plots. In this way, the processes that precede the elections expand the significance of this maintenance game, when the parties and pre-candidates articulate positions within the political field, which implies a transition from a state of non-competitive politics, to a politics of conflict. that will be evidenced by the electoral dispute.